In search of hepatitis E virus infection in wild boar and cattle from Argentina - La Sala, Luciano Francisco; Barandiaran, Soledad; Eirin, Maria Emilia; Ferrara Muñiz, Ximena; Abate, Sergio Damián; Sánchez Puch, Silvia; Mathet, Verónica; Delfino, Cecilia María (Sociedad Argentina para el Estudio de los Mamíferos, 2022)
Hepatitis E virus (HEV) is a pathogen with zoonotic potential that affects domestic pigs, wild boar Sus scrofa, and humans, among other species. The HEV has been reported in wild boar from Argentina and Uruguay, but knowledge about the epidemiology of this virus is still very scarce in this region. The objective of this study was to evaluate the circulation of HEV in wild boar and cattle from Argentina through serological (ELISA) and molecular (PCR) analyses. All samples were negative. However, we stress the importance of reporting negative cases since these represent key inputs in future research and risk analysis, mainly in association with the potential for virus transmission between wild boar and susceptible native species.